84.7k views
0 votes
Find [g ο f](-4) given f(x) = x + 4 and g(x) = -2x2

User Lrathod
by
5.2k points

1 Answer

6 votes

Answer:

Explanation:

(

1

)

.

plugging the

4

into

g

(

x

)

and then putting what you get from that in to

f

(

x

)

(

2

)

.

plug

g

(

x

)

into

f

(

x

)

and then plug in the

4

Option 1:

Plug

4

into

g

(

x

)

:

g

(

x

)

=

2

(

4

)

6

=

8

6

=

14

Then plug

g

(

x

)

into

f

(

x

)

:

f

(

x

)

=

3

(

14

)

7

=

42

7

=

49

Option 2:

Plug

g

(

x

)

into

f

(

x

)

:

f

(

x

)

=

3

(

2

x

6

)

7

=

6

x

18

7

=

6

x

25

Finally plug

4

into our current

f

(

x

)

:

f

(

x

)

=

6

(

4

)

25

=

24

25

=

49

User Kamala
by
5.2k points